Alfonos, García Marqués. Vico. Unidad y principio del saber. Nau llibres. Valencia 1995. 239 páginas. ISBN 84-7642-419-1 - Franck, Juan F. (1999)
Fil: Franck, Juan F. Pontificia Universidad Católica Argentina; Argentina